2010
DOI: 10.1002/mrm.22269
|View full text |Cite
|
Sign up to set email alerts
|

A new paradigm for high-sensitivity19F magnetic resonance imaging of perfluorooctylbromide

Abstract: In the present work, the NMR properties of perfluorooctylbromide are revisited to derive a high-sensitivity fluorine MRI strategy. It is shown that the harmful effects of J-coupling can be eliminated by carefully choosing the bandwidth of the 180°pulses in a spin-echo sequence. The T 2 of the CF 3 resonance of the molecule is measured using a multispin-echo sequence and shown to dramatically depend on the interpulse delay. Following these observations, an optimized multispinecho imaging sequence is derived and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
98
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(102 citation statements)
references
References 22 publications
3
98
1
Order By: Relevance
“…Recently, we developed an optimized MRI sequence dedicated to perfluorooctylbromide (PFOB, sometimes referred to as perflubron), a PFC well-known for its biocompatibility and tested through clinical trials. This sequence takes full advantage of NMR properties of PFOB and yields an excellent sensitivity thanks to massive multiecho accumulation [19]. In addition, it was demonstrated that our sequence was suited to perform accurate in vivo quantitative measurements in the mouse liver and spleen after intravenous (IV) injection of a PFOB emulsion, including oximetry and dynamic biodistribution [20].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, we developed an optimized MRI sequence dedicated to perfluorooctylbromide (PFOB, sometimes referred to as perflubron), a PFC well-known for its biocompatibility and tested through clinical trials. This sequence takes full advantage of NMR properties of PFOB and yields an excellent sensitivity thanks to massive multiecho accumulation [19]. In addition, it was demonstrated that our sequence was suited to perform accurate in vivo quantitative measurements in the mouse liver and spleen after intravenous (IV) injection of a PFOB emulsion, including oximetry and dynamic biodistribution [20].…”
Section: Introductionmentioning
confidence: 98%
“…It is highly sensitive (83 % of the sensitivity of 1 H) and owing to the lack of endogenous fluorine, there is no background signal in 19 F MRI. Therefore, this modality has the unique capability to directly determine concentrations of administrated 19 Fcontaining compounds in tissues. However, only few studies conducted by Waters et al at 11.7 Tesla used a m b 3 -targeted PFC NP in 19 F MRI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the most part, standard pulse-sequence strategies are employed to image fluorine, with slight modifications to excite only particular fluorine resonant frequencies (for molecules with multiple resonant frequencies) [49], or with sequence timing altered to accommodate relaxation rates of perfluorocarbons. In order to obtain reasonable voxel sizes during an in vivo imaging session, dozens or hundreds of averaging scans are often used, resulting in lengthy examination times.…”
Section: Fluorine Mri Acquisitionsmentioning
confidence: 99%
“…), or (3) optimization of acquisition (pulse sequence) techniques for a particular PFC particle construction. For example, Giraudeau et al [49] demonstrated that a reduced bandwidth refocusing pulse is useful to prolong the signal arising from PFOB during a TSE echo-train. anatomical data provided by CT [51,[83][84][85].…”
Section: Introductionmentioning
confidence: 99%